Speaking While Thinking : The Fluency Features Used by Finnish Learners of English While Searching for a Word - Ekman, Essi (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis examined how Finnish upper secondary school learners of English use breakdown and repair fluency features while thinking of what to say or how to formulate their message. The thesis also aimed to see if attending a seven-week spoken English course has an effect on the learners’ use of the features and if their fluency changes during the period. The data consisted of the spoken samples of nine learners that were recorded at the beginning of the English course and seven weeks later at the end of the course. The use of fluency features was studied qualitatively and the change in speed fluency was analysed quantitatively by using statistical methods. The results of the study suggest that Finnish upper secondary school learners use few repair fluency features as a strategy to delay the message. However, they use silent pauses and filled pauses, and also clusters of them while thinking of what to say. The learners rather pause for a long time and eventually deliver their message as accurately as possible than maintain a fluent flow of speech and produce words they would need to reformulate or replace later. The results of the quantitative analysis suggest that the learners’ fluency changed between the pre-test and the post-test in five measures. In the post-test the learners spoke faster, used more AS-unit or clause boundary pauses, spent a greater proportion of the performance speaking, spent less time pausing with silent pauses, and used shorter silent pauses on average. The results of the study cannot be generalised because of the small sample size but the results provide information on the use of fluency features of Finnish learners of English in a narrative monologue. Also, the results suggest that the fluency of learners improves during a short seven-week course but more research is needed to understand the development of fluency and the use of the features.